Dari Struktur Bahasa ke Makna Kontekstual: Analisis Struktural-Linguistik atas Metodologi Tafsir Abdullah Saeed - Rifqatul Husna; M. Rofiqur Rahman (Jurnal Keislaman, 2025)
This study aims to analyze the application of linguistic structuralism principles in Abdullah Saeed’s interpretive methodology as elaborated in his seminal work Interpreting the Qur’an: Towards a Contemporary Approach. The research explores how modern linguistic theory, particularly that of Ferdinand de Saussure, influences the formulation of Saeed’s contextual interpretation of the Qur’an. Employing a qualitative descriptive approach and library research design, the data were analyzed using the Miles and Huberman model, which includes data collection, reduction, display, and conclusion drawing. The findings reveal that linguistic structuralism plays a significant role in shaping Abdullah Saeed’s interpretive framework, especially in viewing the Qur’an as a system of signs whose meaning emerges from the relational interaction between linguistic elements and their socio-historical contexts. Through four systematic interpretive stages—linguistic analysis, historical contextualization, contemporary meaning construction, and practical application of Qur’anic values—Saeed proposes an integrative model that bridges structural linguistics and Qur’anic hermeneutics. The study implies that linguistic structuralism strengthens the scientific and contextual basis of contemporary Qur’anic interpretation. However, the study remains limited to a conceptual analysis of Saeed’s single work. Future research is recommended to conduct comparative studies involving other contemporary exegetes to further test the consistency and applicability of linguistic approaches within Qur’anic exegesis